متطلبات تحقيق الأمن الاجتماعي لكبار السن في الأسرة السعودية - العزام، سهام محمد عبدالله (جامعة الفيوم - كلية الخدمة الاجتماعية, 2023)
هدفت الدراسة إلى تحديد متطلبات تحقيق الأمن الاجتماعي لكبار السن في الأسرة السعودية، من خلال تحديد دور كل من (المدافعة -التمكين -المساندة الاجتماعية -تسويق البرامج الاجتماعية -دعم شبكات الأمن الاجتماعي)؛ كمتطلبات تحقيق الأمن الاجتماعي لكبار السن في الأسرة السعودية. وتنتمي هذه الدراسة إلى نمط الدراسات الوصفية والتي تهدف إلى وصف وتحليل متطلبات تحقيق الأمن الاجتماعي لكبار السن في الأسرة السعودية، وقد اعتمدت الدراسة على منهج المسح الاجتماعي بالعينة لكبار السن في مدينة الرياض، وتحدد مجتمع الدراسة في كبار السن في مدينة الرياض، وشملت عينة الدراسة عينة قومها (٢١٥) من كبار السن المقيمين بمدينة الرياض، واعتمدت الباحثة على أداة الاستبانة لجمع البيانات. وقد أكدت نتائج الدراسة أن دور المدافعة في تحقيق الأمن الاجتماعي لكبار السن في الأسرة السعودية (مرتفع)، وقد جاء بمتوسط حسابي عام (٢,٣٥) وانحراف معياري عام (٠,٦٦)، وقد تمثل في: قدرة كبار السن على المطالبة بحقوقهم في المجتمع عبر المنصات المتعددة، تدعم العادات والتقاليد الإسلامية فكرة المدافعة عن حقوق كبار السن، وأن دور التمكين في تحقيق الأمن الاجتماعي لكبار السن في الأسرة السعودية (متوسط)، وقد جاء بمتوسط حسابي عام (٢,٢٢) وانحراف معياري عام (٠,٨٣)، وقد تمثل في: شعور كبار السن بالراحة والطمأنينة داخل مجتمعهم، العلاقات الاجتماعية لكبار السن جيدة مع الجميع، شعور كبار السن بأهميتهم وتقديرهم لذاتهم في مجتمعهم، وأن دور المساندة الاجتماعية في تحقيق الأمن الاجتماعي لكبار السن في الأسرة السعودية (متوسط)، وقد جاء بمتوسط حسابي عام (٢,٣٠) وانحراف معياري عام (٠,٧٦)، وقد تمثل في: شعور كبار السن بالأمن النفسي داخل مجتمعهم، تلقي كبار السن للمساندة الروحية من القائمين على تقديم الخدمات الدينية في المجتمع، بالإضافة إلى أن دور تسويق البرامج الاجتماعية في تحقيق الأمن الاجتماعي لكبار السن في الأسرة السعودية (مرتفع)، وقد جاء بمتوسط حسابي عام (٢٣٨) وانحراف معياري عام (٠,٨٤)، وقد تمثل في: شعور كبار السن بالأمن عند تقديم البرامج الاجتماعية المناسبة لهم، الإعلان عن برامج رعاية كبار السن يشعرهم بالاهتمام بهم باستمرار، وأن دور شبكات الأمن الاجتماعي في تحقيق الأمن الاجتماعي لكبار السن في الأسرة السعودية (مرتفع)، وقد جاء بمتوسط حسابي عام (٢,٣٢) وانحراف معياري عام (٠,٧٥)، وقد تمثل في: تدعيم الخدمات الحكومية لنظم الرعاية الصحية لكبار السن في المجتمع، إسهام الخدمات الحكومية في التخطيط لمستقبل رعاية كبار السن في المجتمع. The study aimed to determine the requirements for achieving social security for the elderly in the Saudi family, by defining the role of (advocacy- empowerment- social support- marketing social programs- supporting social security networks) as requirements for achieving social security for the elderly in the Saudi family. This study belongs to the style of descriptive studies, which aims to describe and analyze the requirements for achieving social security for the elderly in the Saudi family, sample of (215) elderly people residing in Riyadh, and the researcher relied on the questionnaire tool to collect data. The results of the study confirmed that the role of female advocate in achieving social security for the elderly in the Saudi family is (high), and it came with a general arithmetic mean (2.35) and a general standard deviation (0.66), It was represented in: The ability of the elderly to claim their rights in society Through multiple platforms, Islamic customs and traditions support the idea of defending the rights of the elderly, and that the role of empowerment in achieving social security for the elderly in the Saudi family is (average), and it came with a general arithmetic mean (2.22) and a general standard deviation (0.83), Represented in: the elderly’s sense of comfort and reassurance within their society, the elderly’s social relations are good with everyone, the elderly’s sense of their importance and self-esteem in their society, and that the role of social support in achieving social security for the elderly in the Saudi family is (average), and it came with a general arithmetic average (2.30) and a general standard deviation (0.76), which was represented in: the elderly’s feeling of psychological security within their community, the elderly received spiritual support from those in charge of providing religious services in die community, in addition to the role of marketing social programs in achieving social security For the elderly in the Saudi family (passed F), and it came with a general arithmetic mean (238) and a general standard deviation (0.84), and it was represented in: the elderly’s sense of security when appropriate social programs are provided to them, advertising about elderly care programs makes them feel constantly cared for, and that the role of social safety nets In achieving social security for the elderly in the Saudi family (high), it came with a general arithmetic mean (2.32) and a general standard deviation (0.75), Planning for the future of elderly care in the community.
Keywords: الأمن الاجتماعي -- الرعاية الاجتماعية -- كبار السن -- الأسر السعودية